Comparison Of Rain Attenuation Models For Tropical Climate - Ng , Yun Yann (2010)
The influence of rainfall on radio wave propagation at frequencies above 10 GHz is essential for satellite communication, especially in tropical regions as a result of the high intensity rainfall. Besides, annual and worst month‟s cumulative statistics are needed to give the detailed insights for system design. A three years (from 1st January 2006 until 31st December 2008) rainfall rate and rain attenuation measurement was conducted in Nibong Tebal, Engineering Campus of Universiti Sains Malaysia (USM) (Latitude: 5.170N and Longitude: 100.40E). The cumulative distributions of one-minute rain rate, rain attenuation and worst month statistics analyzed from the USM measured data are presented and compared with existing prediction models.